Productivity and nutrient uptake influenced by different food - forage based cropping system in Kamore Plateau and Satpura hill zone of Madhya Pradesh - Shrivastva, Arati; Jha, A.K.; Jha, Girish (Annals of Agricultural Research, 2016)
The present investigation entitled "Productivity and nutrient up take influenced by different of food-forage based cropping sequence under irrigated conditions of Jabalpur (M.P.)" was conducted at AICRP on forage crops, JNKVV, Jabalpur (M.P.). The experiment was conducted in randomized block design replicated three times with 10 food-forage based cropping sequences. Among ten crop sequences tested maize (baby corn) + ricebean - berseem - maize (baby corn) + ricebean cropping sequence led to record the maximum productivity (2842.37 q/ha/year) in terms of maize green fodder equivalent yield . The crop sequence maize (green cob) + ricebean - berseem - maize (fodder) + ricebean recorded the maximum uptake of N (642.1 q/ha) Total uptake of P was noticed maximum in maize (baby corn) + ricebean - oat - maize (fodder) + ricebean (103.4 q/ha) and minimum in hybrid napier crop sequence (587.9 q/ha). Existing crop sequence rice - berseem - moong registerd (61.2 q/ha) total P uptake.Uptake of K was highest in maize (baby corn) + ricebean - oat - maize (baby corn) + ricebean (757.0 q/ha) and lowest in hybrid napier + ricebean - hybrid napier + berseem- hybrid napier + ricebean (435.9 q/ha).Based on data pertaining to changes in soil properties after completion of 2 crop cycles of various crop sequences were safe to maintain the soil properties. But continuous hybrid napier cropping gave an indication for depletion of OC in the soil after completion of 2 cycles of the rotation. The enhancement in fertility status of soils may be attributed to inclusion of legumes in all crop sequences.